Strategic Model for Improving Instructor Service Quality: The Role of Visionary Leadership, Organizational Culture, Empowerment, Achievement Motivation, and Trust - Zulfikar; Setyaningsih, Sri; Suhendra (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study investigates the influence of visionary leadership, organizational culture, empowerment, achievement motivation, and trust on the quality of instructor services for vocational teachers in the fields of business and tourism in DKI Jakarta. The study focuses on alumni of upskilling and reskilling programs conducted by the Center for Development and Quality Assurance of Vocational Education for Business and Tourism (Balai Besar Pengembangan Penjaminan Mutu Pendidikan Vokasi/BPPMPV Bisnis dan Pariwisata). Using a quantitative approach, the research applies path analysis to examine direct and indirect relationships among variables, with achievement, motivation and trust serving as mediators. Results show that all five independent variables significantly affect instructor service quality, with visionary leadership and organizational culture positively influencing motivation, while organizational culture and empowerment impact trust. To enhance practical applicability, the study employs the Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) to identify priority areas for improvement. The analysis highlights key low-performing indicators—such as responsiveness, assurance, and clarity in leadership vision—that hold high strategic value. The findings contribute a comprehensive and evidence-based model for improving the quality of instructor services in vocational education. Furthermore, this study provides actionable insights for policymakers, training institutions, and educational leaders in developing targeted strategies to improve professional development outcomes and institutional performance.